The Evolving Landscape of Biomarkers in Celiac Disease: Leading the Way to Clinical Development - Smithson, Glennda; Siegelman, Jenifer; Oki, Toshihiko; Maxwell, Joseph R.; Leffler, Daniel A. (Frontiers in Immunology, 2021)
Celiac disease is a common immune-mediated disease characterized by abnormal T cell responses to gluten. For many patients, symptoms and intestinal damage can be controlled by a gluten-free diet, but, for some, this approach is not enough and celiac disease progresses, with serious medical consequences. Multiple therapies are now under development, increasing the need for biomarkers that allow identification of specific patient populations and monitoring of therapeutic activity and durability. The advantage of identifying biomarkers in celiac disease is that the underlying pathways driving disease are well characterized and the histological, cellular and serological changes with gluten response have been defined in gluten challenge studies. However, there is room for improvement. Biomarkers that measure histological changes require duodenal biopsies and are invasive. Less invasive peripheral blood cell and cytokine biomarkers are transient and dependent upon gluten challenge. Here, we discuss established biomarkers and new approaches for biomarkers that may overcome current limitations.